The Impact of Trait Anxiety on Self‐frame and Decision Making†. (18th April 2013) - Peng, Jiaxi; Xiao, Wei; Yang, Yebing; Wu, Shengjun; Miao, Danmin
ABSTRACT The present study investigated how trait anxiety influenced the formation of a self‐frame and decision making. Participants (N = 1044) responded to the Trait Anxiety Inventory. Those with trait anxiety scores ±1 Z score from the sample mean (N = 328) were recalled to respond to the self‐frame questionnaire. The results suggested that trait anxiety differences could result in differences in the editing of decision‐making information, thereby influencing the risky choice. Compared with the low trait anxiety group, participants from the high trait anxiety group showed a greater tendency to use negative vocabulary to construct their self‐frame and tended to choose conservative plans. Self‐frame suppressed the influence of trait anxiety on decision making. These results further confirmed the hypothesis that individual differences in personality traits might influence the processing of information in a framed decision task. Copyright © 2013 John Wiley & Sons, Ltd.